Learning to Analyze the Structure and Language of Anecdotal Texts through the Discovery Learning Method nd the Student Visual Audio Media - Tambulango, Gamaria; Ntelu, Asna; Lamusu, Sance A. (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This paper aims to: (1) Describe the planning, implementation, and assessment of learning with the analysis of the structure and language of anecdotal texts through the discovery learning method and audio visual media; and (2) describe the ability of class X IPS students.1 Analyze the structure and language of anecdotal texts through the discovery learning method and audio visual media. The method used in this study is descriptive-qualitative method. This method is used to describe and present data as it is about the results of research on learning to analyze the structure and happiness of anecdotal texts through the discoveryarning method and audio visual media class X IPS.1 SMA Negeri 1 Boliyohuto. Data collection techniques used in this study are observation techniques, interview techniques, documentation techniques, and test techniques. Data analysis techniques consist of procedures, (1) identify student activities, teachers, learning methods and media used, and the ability of students to analyze the structure and language of anecdotal texts; (2) classifying student learning outcomes in analyzing the structure and language of anecdotal text based on the score category; (3) assessing student learning outcomes in analyzing the structure and language of anecdotal texts; and (4) concluding the results of data analysis. The results of this study indicate that the ability of students in analyzing the structure and language of anecdotal texts has increased. This can be seen from the activity of analyzing the structure of anecdotal text which obtains a value of 90.16 and the language gains a value of 77.60, so that the ability of students to analyze the structure and language of anecdotal text obtained an average value of 83.88. the ability to analyze the structure and language of anecdotal text through the discovery learning method and audio visual media students of class X IPS.1 SMA Negeri I Boliyohuto Tahuan Tahuan 2017/2018 lessons have increased.